Laboratory evaluation of the GreenSeeker handheld optical sensor to variations in orientation and height above canopy - Martin, Daniel E; Lopez Jr., Juan D; Lan, Yubin (International Journal of Agricultural and Biological Engineering, 2012)
Abstract: Handheld optical sensors recently have been introduced to the agricultural market. These handheld sensors are able to provide operators with Normalized Difference Vegetative Index (NDVI) data when cloud cover prevents acquisition of satellite or aerial images. This research addressed the sensitivity of the GreenSeeker handheld optical sensor to changes in orientation and height above a ryegrass canopy. Planter boxes were oriented both parallel and perpendicular to the light beam from the sensor head and heights of 30.5 cm (12